Application of Auto-steering Technology for Tree Planting - Reza Ehsani; Esa Ontermaa (EDIS)
Setting up new orchards or planting new trees on existing beds is one of those orchard operations that have not yet been fully mechanized. Auto-steering technology can be used in conjunction with a tree planting unit to mechanize this operation and reduce tree planting costs. Learn more in this 6-page fact sheet was written by Reza Ehsani and Esa Ontermaa and published by the UF Department of Agricultural and Biological Engineering, March 2011.